The Effect of Inflation, SBI Interest Rate on Foreign Investment (PMA) and Economic Growth in Indonesia (Year 2010-2019) - Al Hanisah Huriah; Arina Jannati Alfina; Lidya Ariska; Nurhasanah; Vina Ananda; Asnidar (PT FORMOSA CENDEKIA GLOBAL, 2023)
The economic crisis experienced by developed countries must be utilized by improving the economic structure in Indonesia to increase economic growth and increase the flow of foreign capital into Indonesia. This study aims to determine the effect of inflation and SBI interest rates on foreign investment and economic growth in Indonesia as an emerging market. The type of research used is explanatory research with a quantitative approach. This study uses 2010–2019 time series data, namely secondary data in the form of data on inflation, interest rates, FDI, and economic growth, which are tested using path analysis techniques. Statistical test results show that the inflation variable has no significant negative effect on FDI; the interest rate has no significant positive effect on FDI; inflation has no significant negative effect on economic growth; the interest rate has no significant positive effect on economic growth; and FDI has a positive and significant effect on economic growth.